Innovative Enhancements in Surface Quality and Hardness of Aluminium Alloy 2024 through an Optimized Burnishing Process - Akbar Hojati (International Journal of Advanced Design and Manufacturing Technology)
The burnishing process showcases a novel approach for significantly improving the surface quality and hardness of metals, particularly aluminium, copper, and brass. This paper presents a novel approach to optimize the burnishing process of Aluminium 2024 by simultaneously analyzing the effects of spindle speed, feed rate, and burnishing force, a comprehensive method that has not been addressed in prior studies. Utilizing a specially designed roller-based tool with a lathe machine, we systematically varied key parameters—spindle speed, feed rate, and burnishing force—through a full factorial design with two repetitions. Advanced statistical analysis was conducted using Minitab software to assess the effects of these parameters on surface roughness and hardness, employing regression methods for precise predictions. Remarkably, the results demonstrated that optimal surface roughness (Ra = 0.05 μm) was attained at a feed rate of 0.11 mm/rev, spindle speed of 1000 r/min, and burnishing force of 1000 N. This research not only highlights the effectiveness of the burnishing process in enhancing the mechanical properties of aluminium alloys but also introduces innovative methodologies that pave the way for improved industrial applications. Future studies will investigate the effects of burnishing in corrosive environments and its impact on material strength.